The importance of English language : The importance of English language - Xamrayeva, Umida Xamrayeva (Maktabgacha taʼlim jurnali, 2020)
One of the main factors of globalization is direct communication of different nations and peoples with each other. Serious, intensive, effective study of foreign languages plays an important role in this.